Overview of livestock biogas technology development and implementation in Thailand - P. Aggarangsi (2018)
In this paper, the implementation of biogas technologies in animal farms in Thailand and the government policies used to promote these technologies are presented. The Thai government has created a goal of achieving 14% of all energy needs from renewable resources by 2022. As a renewable technology, biogas has the potential to reduce Thailand's dependence on fossil fuels which make up over 90% of Thailand's electricity generation. An unfortunate by-product from animal farm waste is the greenhouse gas, methane. The benefits from capturing and utilizing this gas include increased electric generation, less odor in the local community, less greenhouse gas emissions, more revenue for farmers and production of raw fertilizer material. Thailand has the potential to produce over onebillionm 3 of biogas per annum from its agricultural industry alone. Current utilization is only 36% of this potential. This paper will briefly discuss the technology used to capture and use biogas from animal farms in Thailand. The effect of government policies on this technology deployment shall be discussed. This paper demonstrates how technology and policy need to work together in order to best provide a practical solution for energy problems. In 2012, greenhouse gases worth 1400Gg CO 2 equivalent were saved from entering the atmosphere from animal farms in Thailand. © 2013 International Energy Initiative.